Benchmarking HIV health care: from individual patient care to health care evaluation. An example from the EuroSIDA study - Podlekareva, Daria N; Reekie, Joanne; Mocroft, Amanda; Losso, Marcelo; Rakhmanova, Aza G; Bakowska, Elzbieta; Karpov, Igor A; Lazarus, Jeffrey V; Gatell, Jose; Lundgren, Jens D; Kirk, Ole (BMC infectious diseases, 2012)
Background State-of-the-art care involving the utilisation of multiple health care interventions is the basis for an optimal long-term clinical prognosis for HIV-patients. We evaluated health care for HIV patients based on four key indicators. Methods Four indicators of health care were assessed: Compliance with current guidelines on initiation of: 1) combination antiretroviral therapy (cART); 2) chemoprophylaxis; 3) frequency of laboratory monitoring; and 4) virological response to cART (proportion of patients with HIV-RNA < 500copies/ml for >90% of time on cART). Results 7097 EuroSIDA patients were included from Northern (n = 923), Southern (n = 1059), West Central (n = 1290) East Central (n = 1366), Eastern (n = 1964) Europe, and Argentina (n = 495). Patients in Eastern Europe with a CD4 < 200cells/mm 3 were less likely to initiate cART and Pneumocystis jiroveci -chemoprophylaxis compared to patients from all other regions, and less frequently had a laboratory assessment of their disease status. The proportion of patients with virological response was highest in Northern, 89% vs. 84%, 78%, 78%, 61%, 55% in West Central, Southern, East Central Europe, Argentina and Eastern Europe, respectively (p < 0.0001). Compared to Northern, patients from other regions had significantly lower odds of virological response; the difference was most pronounced for Eastern Europe and Argentina (adjusted OR 0.16 [95%CI 0.11-0.23, p < 0.0001]; 0.20[0.14-0.28, p < 0.0001] respectively). Conclusions This assessment of HIV health care utilization revealed pronounced regional differences in adherence to guidelines and can help to identify gaps and direct target interventions. It may serve as a tool for the assessment and benchmarking of the clinical management of HIV patients in any setting worldwide.